1991
DOI: 10.1007/bf00371777
|View full text |Cite
|
Sign up to set email alerts
|

Keratohyalin granules are heterogeneous in ridged and non-ridged human skin: evidence from anti-filaggrin immunogold labelling of normal skin and skin of autosomal dominant ichthyosis vulgaris patients

Abstract: Recent biochemical and morphological investigations have provided evidence for a heterogeneous composition of keratohyalin in human skin. A major component is filaggrin. In interfollicular epidermis the heterogeneity of keratohyalin is not directly visible, whereas in normal ridged skin bicomponent keratohyalin is revealed by electron microscopy. Skin biopsies of ridged and non-ridged skin of normal individuals and patients with autosomal dominant ichthyosis vulgaris (ADI)--characterized by defective keratohya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
1
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
2
7
1
2
Order By: Relevance
“…When KHG were present, ultrastructural abnormalities were not detected. The differences between these observations and those reported previously (21,22,34,35), in which ‘crumbly’ KHG were observed, appear to reflect differences in technique. This is supported by the demonstration of a small amount of immunoreactive profilaggrin in the epidermis of an individual with IV and no KHG by immunoelectron microscopy (36).…”
Section: Discussioncontrasting
confidence: 89%
“…When KHG were present, ultrastructural abnormalities were not detected. The differences between these observations and those reported previously (21,22,34,35), in which ‘crumbly’ KHG were observed, appear to reflect differences in technique. This is supported by the demonstration of a small amount of immunoreactive profilaggrin in the epidermis of an individual with IV and no KHG by immunoelectron microscopy (36).…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, some reports previously suggested that keratohyalin granules are heterogeneous and bicomponent in human skin. In fact, keratohyalin consists of a major electron-dense component containing filaggrin and a less electron-dense minor component without filaggrin (Günzel et al 1991; Kastl and Anton-Lamprecht 1990). Although we were not able to analyze keratohyalin granules in our samples, we may hypothesize that keratohyalin may be heterogeneous in normal human skin, especially in ridged skin, as suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Filaggrin deficiency is well known in ichthyosis vulgaris (Gunzel et al, 1991). Defective interaction between keratin and filaggrin is also seen in epidermolytic hyperkeratosis.…”
Section: Discussionmentioning
confidence: 99%